2019
DOI: 10.1177/1049732319862532
|View full text |Cite
|
Sign up to set email alerts
|

Fixed Nodes of Transience: Narratives of Homelessness and Emergency Department Use

Abstract: Discourse in popular media, public policy, and academic literature contends that people who are homeless frequently make inappropriate use of hospital emergency department (ED) services. Although researchers have investigated the ED experiences of people who are homeless, no previous studies have examined how this population understands the role of the ED in their health care and in their day-to-day lives. In the present study, 16 individuals participated in semistructured interviews regarding their ED experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“… 480 , 484 , 488 , 493 , 494 , 500 , 509 , 526 , 535 , 539 Four (7%) observational studies looked into ED provider perspectives, 515 , 520 , 523 and two looked into homeless patient perspectives on ED services. 482 , 483 A few studies focused on specific sub-populations of homeless patients, including veterans, 492 , 519 , 524 , 528 older adults, 499 , 501 and pediatric patients. 485 , 486 , 507 , 534 Two (40%) interventional studies centered on analyzing the effect of case management interventions on ED utilization.…”
Section: Resultsmentioning
confidence: 99%
“… 480 , 484 , 488 , 493 , 494 , 500 , 509 , 526 , 535 , 539 Four (7%) observational studies looked into ED provider perspectives, 515 , 520 , 523 and two looked into homeless patient perspectives on ED services. 482 , 483 A few studies focused on specific sub-populations of homeless patients, including veterans, 492 , 519 , 524 , 528 older adults, 499 , 501 and pediatric patients. 485 , 486 , 507 , 534 Two (40%) interventional studies centered on analyzing the effect of case management interventions on ED utilization.…”
Section: Resultsmentioning
confidence: 99%
“…Earlier research found that members of EDGs, such as Indigenous peoples [ 28 , 29 ] and the vulnerably housed [ 6 , 14 ], perceived that they experience longer wait times in the ED. However, our study does not support these findings, with members of EDGs not perceiving that they had different wait times than controls (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While anecdotal evidence exists, empirical data to document and understand systemic racism within Canadian healthcare is lacking. Existing research primarily consists of smaller qualitative studies, often without the inclusion of controls to provide insights about how EDGs perceive their care in comparison to those who do not identify as equity-deserving [ 6 , 7 , 13 , 14 ]. The Kingston Health Sciences Centre’s (KHSC) ED and urgent care centre (UCC) serve as the sole points of emergency care provision for patients who are members of EDGs in Kingston, Ontario, a city recognized for its income and quality of living disparities [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, despite widespread implementation of HCH programs, barriers to care in homeless populations persist and engaging and retaining individuals experiencing homelessness in primary care remains a challenge. Qualitative studies have identified barriers to primary care retention ranging from stigma, distrust of medical professionals, prior negative encounters with rejection, to competing priorities, and logistical complexity [7][8][9]. Mental illness has also been shown to be a barrier to receiving primary care, with substance abuse, trauma, personality and/or psychiatric disorders contributing to the psychological vulnerability of this population [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%